2011
DOI: 10.1002/jssc.201100162
|View full text |Cite
|
Sign up to set email alerts
|

Enthalpy–entropy compensation effect on adsorption of light hydrocarbons on monolithic stationary phases

Abstract: Enthalpy and entropy of adsorption of light hydrocarbons C1-C4 have been measured for three monoliths of different polarity and for five different carrier gases: helium, hydrogen, nitrogen, carbon dioxide and dinitrogen oxide. Using carrier gas helium the highest values of enthalpy and entropy were observed for monolith based on ethylenedimethacrylate and the lowest values were observed for monolith based on silica, while monolith based on divinylbenzene demonstrated intermediate values. Entropy-enthalpy corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Studies have shown that EEC also occurs during the adsorption of low molecular weight gases on active surfaces (Burevski et al 1991;Fletcher and Thomas 2000;Garrone et al 2008;Korolev et al 2011;Hercigonja and Rakić 2013;Pera-Titus 2016;Zukal et al 2009;Kelut et al 2014), wherein the dependence isn't necessarily linear, as Eq. (1) in unequivocal manner (Fletcher and Thomas 2000;Garrone et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that EEC also occurs during the adsorption of low molecular weight gases on active surfaces (Burevski et al 1991;Fletcher and Thomas 2000;Garrone et al 2008;Korolev et al 2011;Hercigonja and Rakić 2013;Pera-Titus 2016;Zukal et al 2009;Kelut et al 2014), wherein the dependence isn't necessarily linear, as Eq. (1) in unequivocal manner (Fletcher and Thomas 2000;Garrone et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…= 34.6 • C, dipole moment = 1.15 D) was the first eluent, followed by . The BuMA-co-EDMA monolith is mainly apolar, but it is more polar than silicate stationary phases [28][29][30], which led to a faster elution of the more polar acetone than the less polar dichloromethane, despite the lower b.p. of the latter.…”
Section: Chromatographic Performancementioning
confidence: 98%
“…The influence of carrier gases on separation processes in general has been discussed in some publications. Joseph et al investigated the adsorption of propane, butane, and Freon-12 on an activated carbon from the carrier gases helium, nitrogen, and carbon dioxide at 17.4 °C and ambient pressure . The data show that with increasing adsorption of the carrier gas, a significantly lower loading of the target component is achieved (He < N 2 < CO 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Under the assumption that helium hardly adsorbs, Joseph et al described the isotherms from the carrier gas helium as pure component isotherms. Korolev et al determined increasing adsorption enthalpies for a series of carrier gases on a silicalite in the order H 2 > He > N 2 > CO 2 > N 2 O, and helium was selected as the quasi-ideal, best possible carrier gas …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation